The Recent Economic Performance of Ukrainian Immigrants in Canada and the U.S. - Sergiy Pivnenko; Don J. DeVoretz (Institute for the Study of Labor (IZA), 2003)
This paper explores the relative success of ethnic and immigrant Ukrainians in Canada and in the United States. We found evidence for both a sheepskin and citizenship effects, which partially explains the strong economic performance of Ukrainian immigrants in Canada. Ukrainian immigrants to the U.S. are overachievers relative to all groups, which sheds light on Borjas thesis that self-selection and not immigration policy sorts immigrants between Canada and the U.S.
Keywords: J61; J31; 330; immigration; earnings; ethnicity; assimilation; Einwanderung; Ukrainer; Soziale Integration; Einkommen; Erfolgsfaktor; Kanada; Vereinigte Staaten